Involvement of Pruritus, Gut Dysbiosis and Histamine-Producing Bacteria in Paraneoplastic Syndromes - Doina Georgescu; Daniel Lighezan; Mihai Ionita; Paul Ciubotaru; Gabriel Cozma; Alexandra Faur; Ioana Suceava; Oana Elena Ancusa; Roxana Buzas (Biomedicines)
Background/Objectives: Paraneoplastic syndromes (PNS), characterized by a large diversity of symptoms, may sometimes be the first clinical feature of a severe underlying disorder such as cancer. Methods: We report the case of a middle-aged male patient with no significant previous medical history, a nonsmoker or alcohol heavy drinker, complaining about generalized, recently onset itch. Given no reasonable explanation of pruritus after dermatological consultation and the unsatisfactory response to treatment, the patient was referred to gastroenterology with the suspicion of a cholestatic liver disease. Results: The abdominal ultrasound examination revealed gallstones and no dilation of the biliary tree. Numerous tests were run and came out negative, except for the slight elevation of C-reactive protein, mild dyslipidemia, and positivity for H. pylori antigen. The gut microbiota displayed important dysbiosis with a significant increase in the histamine-producing bacteria. Given this chronic pruritus became suspicious, thorax and abdominal CT were recommended and performed soon after. A large right mid-thoracic tumor image was found. Bronchoscopy came out negative for a tumor. After the CT-guided biopsy, the tumor turned out not to be a lymphoma, but a non-small cell lung carcinoma (NSCLC). Conclusions: Chronic pruritus was not associated with cholestasis in a patient with gallstone disease, but rather with a PNS, as the first clinical manifestation of NSCLC, triggering many diagnostic and therapeutic challenges.